The saturation effect of a body shape index on lumbar bone mineral density in US adults: Findings from a nationwide survey - Ziyi Zhao; Hongxiang Ji; Wenyu Liu; Zhengdan Wang; Shengquan Ren; Chunlei Liu; Caifeng Wu; Jian Wang; Xiaoheng Ding (PLoS ONE, 2025)
Background Many studies have demonstrated that obesity is closely linked with bone metabolism. A body shape index (ABSI) is a newly developed obesity indicator, which provides superior reflection of central obesity compared to body mass index (BMI) and waist circumference. Nevertheless, investigation of the association between ABSI and bone mineral density (BMD) remains limited. Thus, this study aimed to evaluate the correlation between ABSI and lumbar BMD among US adults. Methods We analyzed data of adults aged 20 years and older from 2011–2018 National Health and Nutrition Examination Survey. Weighted multiple regression analysis was conducted to assess the linear relationship between ABSI and lumbar BMD. Weighted smooth curve fitting and two-segment linear model were applied to explore the nonlinear association. Subgroup analysis stratified by age, gender, race, and BMI was performed. Results A total of 10991 subjects was enrolled in the study. In the fully adjusted model, the ABSI was negatively related to lumbar BMD (β = −0.007, 95% CI: −0.009, −0.005). The adverse correlation remained significant across all subgroups among stratified analysis. The saturation effect between ABSI and lumbar BMD was identified, with the turning point at the ABSI value of 0.08. Similar nonlinear trends were also observed in participants aged <40 years, males, Non-Hispanic White, BMI < 25 kg/m2, and BMI ≥ 30 kg/m2. Conclusion This study revealed a prominently negative correlation and saturation effect between ABSI and lumbar BMD in US adults. Our findings may provide valuable inspiration for further prevention and intervention of osteoporosis.